Policy issues for Australia’s education systems: Evidence from international and Australian research - Marks, Gary N.; McMillan, Julie; Ainley, John (Education Policy Analysis Archives, 2004)
Our purpose here is to discuss education policy issues in the context of empirical evidence. We note that many commonly held beliefs about Australian education such as, the relative performance and participation levels of Australian students; the importance of socioeconomic background on educational outcomes both relative to other countries and changes over-time; gender differences in mathematics and science; and the labour market situation of early school leavers; are not supported by empirical research. Such findings have implications for government policies. We also question current policy directions toward increasing Year 12 participation, expanding both secondary and post-secondary vocational education and reducing class sizes. It is hoped that the discussion will provide stimulus to evidence-based debates about Australian education.